O uso da medicina tradicional chinesa na ampliação da anamnese: a espiritualidade, as emoções e a clínica na saúde do idoso - Leite, Silvia Regina Rodrigues (2014)
The National Policy on Integrative and Complementary Practices (PNPIC) was implemented by the National Health System (SUS) in 2006, creating a range of possibilities to ensure the integrality in the health care practises. The medical training needs to be done so the student learn to look the person who he is taking care in a holistic way, in view of the current reality of showing the direction of the medical knowledge, because the practice is grounded in the biomedical conception. One starts from the assumption that the Traditional Chinese Medicine approaches enable to qualify the anamnesis, especially in elderly patients, in order to take into account their lifestyles, their emotions and their spirituality. The themes linked to the integrative practises should be debated in the academia, since the new medical training program searches for new perspectives of professional education. The goal of this thesis is to analyze the use of the Traditional Chinese Medicine on broadening the anamnesis done by medicine students, on medical visits for the elderly people on the Family Health Strategy. Its specific goals were: to know the anamnesis meaning for medicine students on elderly patients; to offer training to the students for the clinical handling under the Traditional Chinese Medicine light and to identify changes on the medical practice after the training offered. It is an action-research, with qualitative approach, with eight medicine students from a private college as subjects, during their internship of public health, carried out in a unit of family health in the cities of Cabedelo and João Pessoa, both on Paraíba State. In relation to the data collecting, in the first stage, recorded interviews were performed with the use of a semi-structured script. In the second phase, training was offered to the students to develop the anamnesis of the elderly, according to the techniques of Traditional Chinese Medicine. In the third stage, newly recorded interviews were conducted. To analyze the data, content analysis technique was used, on the theme mode. It was identified through the results that students have weaknesses in their approach with the patient and in his training, at the prospect of comprehensive, humane care and practiced with the use of knowledge of the integrative practices. We also observed little appreciation of the semiology knowledge needed to develop a wider anamnesis, according to the holistic concepto of health. However, the students were receptive to the new knowledge, when invited to attend the training in Traditional Chinese Medicine. In this respect, it was verified that the training conducted caused students to include new information about anamnesis theme, which leads to recommend educational strategies focused on action-research, could be employed in medical education in order to strengthen changes in the health care model.